Comparative efficacy and safety of 180 W XPS vs. 120 W HPS GreenLight laser therapy for benign prostatic hyperplasia: a systematic review and meta-analysis - Min Wang; Yu Xi; Zan Qiu; Nanxiang Huang; Li Zhang; Jinlong Liu (PeerJ)
Objectives To compare the surgical and functional outcomes of the 120 W HPS and 180 W XPS GreenLight laser vaporization systems in the treatment of benign prostatic hyperplasia (BPH). Methods In January 2024, a comprehensive search across PubMed, Cochrane Library, and EMBASE was conducted following PRISMA guidelines, registered under PROSPERO (CRD42024531176). Studies comparing 120 W and 180 W GreenLight lasers in BPH treatment were assessed for clinical outcomes. Results Eight studies were included. The 180 W XPS system improved operation time (MD: 12.70, 95% CI [5.29–20.11], p = 0.0008), lasing duration (MD: 10.09, 95% CI [0.85–19.33], p = 0.03), and catheterization duration (MD: 0.43, 95% CI [0.12–0.74], p = 0.007). No significant differences in energy consumption, energy density, or length of hospital stay were found. Functional outcomes such as International Prostate Symptom Score and maximum urinary flow rate showed no significant differences, except in quality of life (MD: 0.43, 95% CI [0.06–0.80], p = 0.02) and prostate-specific antigen levels (MD: −0.77, 95% CI [−1.28 to −0.25], p = 0.003). The 180 W system exhibited a lower rate of overall (OR: 1.52, 95% CI [1.14–2.04], p = 0.005) and minor complications (OR: 1.84, 95% CI [1.27–2.66], p = 0.001), with no significant differences in major complications or other adverse events. Conclusions The 180 W XPS system demonstrates enhanced efficiency and reduced complication rates, offering a favorable option for BPH treatment, particularly for larger prostates. Future studies should focus on randomized trials to confirm these findings and assess long-term outcomes.